Tinjauan Pelanggaran Kode Etik Notaris Kota Medan Menurut Perspektif Pengawasan Majelis Pengawas Daerah Notaris - Leonard, Tommy; Azharuddin, Azharuddin; Wilbert, Wilbert (Jurnal Suara Hukum, 2023)
The Notary's Code of Ethics is a guideline for the attitude and behavior of a notary. It is necessary to maintain the quality of legal services to the public. The supervision of notaries is done by the Notary Supervisory Board to ensure that notaries always act in accordance with the legal principles that underlie their authority and avoid abuse of the authority or trust given. This empirical judicial research collects data from library and field research. The research results of this study show that there are 54 (fifty four) complaints receieved by Notary Supervisory Board in Medan from 2018 until 2021. The supervision is based on Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number: M.02.PR.08.10 of 2004, Ministerial Decree Law and Human Rights of the Republic of Indonesia Number M.39-PW.07.10. 2004 and the role of the Regional Supervisory Board includes preventive purposes, namely reflecting on the position of the Notary Ethics Code in order to provide material related to the implementation of the position of Notary, participating in seminars, and checking Notary protocols.